Pengaruh Diferensiasi Produk,Penetapan Harga,dan kualitas Produk Terhadap Keputusan Pembelian Produk - Zuzmawati Zuzmawati; Silvi Wulandari (STAI YPIQ BAUBAU, SULAWESI TENGGARA, 2024)
The purpose of this study was to examine product differentiation on product purchasing decisions (Case Study at the Padang Center Batik Palace), to test pricing for product purchasing decisions (Case Study at the Padang Center Batik Palace), to test product quality on product purchasing decisions (Case Study at the Palace of Batik Center Padang). Type of Research This type of research is in the form of quantitative research. Sampling method using the lemeshow formula as many as 100 respondents. Data analysis techniques used were validity, reliability, descriptive analysis, normality test, multicollinearity test, heteroscedasticity test, multiple regression analysis, and t test. The results of the study show that differentiation has a positive and significant effect on product purchasing decisions (Case Study at the Batik Center Palace in Padang). Pricing has a positive and significant effect on product purchasing decisions (Case Study at the Palace of Batik Center Padang). And product quality has a positive and significant effect on product purchasing decisions (Case Study at the Padang Center Batik Palace).